Modified bovine serum albumin as an effective charge-reversal platform for simultaneously improving the transfection efficiency and biocompatibility of polyplexes. Issue 23 (21st June 2015) - Zhang, Tingbin; Song, Xiaoyan; Kang, Di; Zhang, Ling; Zhang, Chunqiu; Jin, Shubin; Wang, Chongxi; Tian, Jianhua; Xing, Jinfeng; Liang, Xing-Jie
<x xml:space="preserve">Abstract</x> An excellent charge-reversal material base on BSA was used to reduce the cytotoxicity of polyplexes and improve their gene transfection efficiency at the same time.